Sleep disturbances in nurses enrolled in part-time studies - Tomaszek, Tomaszek; Cepuch, Grażyna; Fugie, Beata (Nursing in the 21st Century, 2015)
SLEEP DISTURBANCES IN NURSES ENROLLED IN PART-TIME STUDIESAim. The aim of this study was to assess the prevalence of sleep disorders among nurses enrolled in part-time studies and to identify the key factors affecting the sleep quality.Material and methods. The study was conducted on part-time student-nurses majoring in nursing. Sleep disorders were described using the Athens Insomnia Scale and the FIRST scale, as well as the author’s questionnaire. Data were analysed using Mann-Whitney U tests, ANOVA, Kruskal-Wallis and appropriate post-hoc tests. A significance criterion of P